Approaches for integrating information from radiation biology and epidemiology to enhance low-dose health risk assessment : recommendations of the National Council on Radiation Protection and Measurements. (NCRP report ;, 2020)
"This Report extends the concepts and approaches discussed in NCRP Report No. 171 and Commentary No. 24 to further reduce uncertainty in radiation risk assessments at low doses and low dose rates, thereby enhancing the bases for radiation protection guidance"--